Blood Eosinophil Count as a Diagnostic and Severity Biomarker in Bronchial Asthma: Correlations with Pulmonary Function and Peripheral Oxygen Saturation - Talib, Ali. M.; Shaheed, Orass. M. (American Journal of Biology and Natural Sciences, 2026)
Airway eosinophilic inflammation characterizes the leading phenotype of adult asthma, and BEC is considered a convenient biomarker for representing the level of underlying airway inflammation and severity of asthma. The current case-control study was carried out among adults visiting Al-Diwaniyah Teaching Hospital from October 2024 to March 2025. Participants included patients of bronchial asthma with subgroups of different severity (mild, moderate, and severe asthma) and an equal number of control subjects without any underlying disease. Blood eosinophils were measured by automated five-part differential count test. Spirometric indices, including FEV₁%, FVC%, FEV₁/FVC, as well as peripheral oxygen saturation, were evaluated among all participants. BEC was found to be significantly elevated in asthmatic patients as compared to control participants (2.5 times greater). Furthermore, the increase was statistically significant and exhibited a stepwise trend along with increasing severity subgroups with the rising eosinophilic inflammatory process (P < 0.001, Kruskal-Wallis). Inverse significant correlation was detected between BEC and all evaluated indices – FEV₁%, FVC%, FEV₁/FVC, as well as SpO₂, while positive correlations were obtained with duration and exacerbations of asthma (all P < 0.001). ROC curve analysis revealed high accuracy of BEC for diagnosing asthma (area under the curve = 94.8%; 95% CI: 90.7–99.0%) and an appropriate trade-off between sensitivity (90.0%) and specificity (88.3%).